Jak definovat zkřivení křivky - Zahrádka, Jaromír (Univerzita Pardubice, 2004)
The first, the second and the total distortions of the curve of finite lenght are quontities that are defined as the path integrals of functions of the first, the second, and the third curvature over the all points of the given curve. The middle first, the middle second, and the middle total distortions of the curve are quotients that are defined as the first, the second, and the total distortions divided by lenght of the given curve.
Keywords: analytická geometrie; křivky; definice